The faithful librarian : essays on Christianity in the profession - Trott, Garrett B., 1973-; Smith, Gregory A., 1972- (McFarland & Company, Inc., 2019)
"What do Christianity and librarianship have in common? Netherlands Prime Minister and theologian Abraham Kuyper (1837-1920) was among the first in the modern era to attempt to rejoin the dichotomy of sacred vs. secular study when he said, "no single piece of our mental world is to be hermetically sealed off from the rest." Over the years a number of publications have followed Kuyper's lead yet little has been written on the subject since Greg A. Smith's notable Christian Librarianship (2002). Building on Smith's work, this volume seeks to bridge the sacred/secular divide with an exploration of how Christianity and the gospel are manifested through the profession of librarianship."--